Design and fabrication a mould for tensile testing for powder specimen - Mohd Ayub, Adnan (2007)
Development of this mould is to produce a tensile test specimen in the form of powder that according to the American Standard of Testing and Material (ASTM). Students can make the specimen on themselves and determine the tensile stress of the specimen by doing some experiments. The punch and die are made from Stavax steel and for the base and stand, they are made from mild steel. Whole of this project is particular involves the mould. Diploma final year project will allocate one semester to complete the project. This project also required the adequate student to finish a task given. The tasks division need to be applied, for the entirely two part will be make that is a process to development of parts and assemble the mould. In conclusion, this project has achieve its goal through the successful of the product making.